Spectroscopic Ellipsometry Characterization and Radiative Limit Modeling of Bismuth-Based Perovskite-Inspired Absorbers for Indoor Photovoltaics - Kamppinen, Aleksi; Grandhi, G. Krishnamurthy; Hadadian, Mahboubeh; Toikkonen, Sami; Yli-paavola, Sirius; Vivo, Paola; Miettunen, Kati (Wiley-VCH, 2026)
Lead-free bismuth-based perovskite-inspired materials (Bi-PIMs) are emerging as wide bandgap semiconductors for sustainable optoelectronic applications, including indoor photovoltaics (IPVs). Computational modeling is a powerful tool to understand and optimize their device performance. However, device-relevant thin film optical constants for these absorbers remain scarce, limiting quantitative optical and electrical design. Here, for the first time the optical constants of two promising thin-film Bi-PIMs—Cu2AgBiI6 and Cs3Bi2I6Br3— are determined using spectroscopic ellipsometry. The applied graded effective medium approximation model is supported by the atomic force microscopy and scanning electron microscopy characterizations of varying film thicknesses. A realistic planar device stack is then simulated under both AM1.5G solar and 1000 lx indoor spectra. Under indoor conditions (1000 lx, 4000 K color temperature), the optical photocurrent limits are ca. 91 µA cm−2 for Cu2AgBiI6 and ca. 32 µA cm−2 for Cs3Bi2I6Br3 with the corresponding radiative-limit efficiencies of ca. 42 % and ca. 18 %, respectively. These results reveal a significant optical margin and motivate efforts to suppress nonradiative recombination and improve charge transport. More broadly, the extracted optical constants enable accurate photogeneration estimation for optoelectronic device modeling, providing insights into current performance limitations of Bi-PIM devices and guiding strategies to overcome them.